Taxa de desenvolvimento de Chrysomya albiceps(Wiedemann) (Diptera: Calliphoridae) em dieta artificial acrescida de tecido animal para uso forense - Estrada, Dora A.; Grella, Maicon D.; Thyssen, Patricia J. [UNESP]; Linhares, Aricio X. (Entomological Soc Brasil, 2009)
Forensic entomology uses biological and ecological aspects of necrophagous insects to help in criminal investigations to estimate the post-mortem interval (PMI) or to determine the cause of death. Recent papers demonstrated that the presence of toxins in decomposing tissues may alter the insect developmental rate of insects exploiting such tissues as food. Thus, preliminary tests with artificial diets in laboratory are necessary to create a database to investigate and quantify the modifications that can occur with the collected insects from a criminal scene, avoiding any errors on the PMI estimates. The present study aimed to evaluate the developmental rate of Chrysomya albiceps (Wiedemann) reared on: a) artificial diets containing animal tissues: bovine liver (D1), raw muscle (D2), stomach (D3), and chicken heart (D4); b) artificial diet without animal tissue (D5); and c) a control group (C), which had only meat. The efficiency of each substrate was assessed by immature weight gain (mg), larval developmental time, larval and pupal survival, emergence interval and adult size. D1 to D4 diets did not restrict C. albiceps development; however, larvae reared on D1 and D2 diets presented a lower adult emergence rate. D3 and control group showed similarities regarding the efficiency parameters (rate and emergence interval). Thus, the use of diet D3, artificial diet with stomach, is the most recommended.
Chrysomya albiceps (Wiedemann) (Diptera: Calliphoridae) Developmental Rate on Artificial Diet with Animal Tissues for Forensic Purpose
Keywords: Nutritional source; immature rearing; blowfly; forensic entomology